An unusual case of chronic lymphocytic leukemia, multiple myeloma and cardiac amyloidosis - Dongyan Liu; Hakim T. Uqdah; Alisha D. Gordy (Greater Baltimore Medical Center, 2017)
Light chain amyloidosis has very rarely been reported in association with chronic lymphocytic leukemia (CLL). We reported on a 76-years-old female who presented with simultaneous kappa-restricted chronic lymphocytic leukemia (CLL) and a lambda-restricted multiple myeloma with plasma cells causing AL amyloidosis involving the heart. While monoclonal immunoglobulins occasionallyproduced by CLL have previously been implicated in AL amyloidosis, there only a few cases reported of AL amyloidosis resulting from a distinct plasma cell dyscrasia that is not clonally related to the concurrent CLL.